CLINICAL IMPORTANCE OF MICROMETASTASIS IN SENTINEL LYMPH NODE - Beyza Özçınar; Mahmut Müslümanoğlu; Abdullah İğci; Sibel O. Gürdal; Ekrem Yavuz; Mustafa Keçer; Temel Dağoğlu; Vahit Özmen (European Journal of Breast Health, 2009)

(untitled)
Introduction: The axillary lymph node status is still the most important accepted prognostic factor in the staging and treatment of breast cancer, although some controversies exist regarding tumor characteristics. In this study, we have evaluated the incidence of micrometastasis and nonsentinel lymph node metastasis, and local and axillary recurrence rate of these patients after completed level I-II axillary lymph node dissection.Materials and Methods: Between January 2000 and June 2008, 760 patients with early stage breast cancer underwent sentinel lymph node biopsy were evaluated and 45 patients (6.0 %) with micrometastasis (0.2-2.0 mm) in sentinel lymph node biopsy included in this study. Patients with negative SLNs determined by hematoxylin and eosin staining were evaluated further examination with cytokeratin immunohistochemistry to detect micrometastasis and isolated tumor cells. Data concerning tumor and patients’ characteristics and adjuvant treatment of these patients were recorded.Results: Median age was 46 (26-67) years, median tumor size was 20 (1-50) mm, and median number of excised sentinel lymph nodes were 2 (1-5). All patients with micrometastasis underwent further level I-II axillary lymph node dissection. In 11/45 (24.4 %) patients with micrometastasis in their sentinel lymph node biopsy had nonsentinel lymph node metastasis after an axillary lymph node dissection and the mean metastatic lymph node number was 1,2 (1-9). The factors related with nonsentinel lymph node metastasis were examined (age, tumor size, quadrant, histologic grade, lymphovascular invasion, histopathologic type, receptor status, multifocality/multicentricity, and the size of micrometastasis). There was no factor found to be related with nonsentinel lymph node metastasis. Stage migration occurred in 4 out of 45 patients (8.8%) due to the detection of micrometastasis or macrometastasis in nonsentinel lymph nodes, however, adjuvant chemotherapy regimen was not changed in these patients. The radiation therapy fi eld was extended due to detection of 4 or more metastatic lymph nodes. The median follow up time was 19 (6-113) months and there was no axillary recurrence detected during this period.Conclusions: The classical opinion after detection of micrometastasis in sentinel lymph nodes was further axillary dissection. However, non randomised, non prospective studies with 4-5 year follow up time showed 0.6 % of axillary recurrence without further axillary lymph node dissection. However, still we need the results of randomized, prospective studies.